Tribological Characteristics of Carbon Nanotubes-Reinforced Plasma-Sprayed Al2O3-TiO2 Ceramic Coatings. (7th September 2021) - Kalangi, Chaitanya; Bolleddu, Venkateshwarlu; Allasi, Haiter Lenin
Abstract : Thermal-sprayed coatings are widely used in various oil and gas industries for wear and corrosion applications. However, increasing performance and requirements make conventional coatings inadequate for future needs. Furthermore, the heat conductivity of bulk materials cannot be minimized easily. Therefore, the use of low porous coating with nanocomposite doping is an effective way to produce coatings with reduced thermal conductivity. Plasma-sprayed Al2 O3 -TiO2 coatings are found in a wide range of applications recently in many industries because of their exceptional properties including low expenses and ease of availability. In this work, the wear-resistant and low porous coatings of Al2 O3  + 3 wt%TiO2 and respective carbon nanotube (CNT) doped coatings are prepared and characterized. The coatings are deposited on the AISI 1020 steel substrate using air plasma spraying. The impact of CNTs reinforcement on the percentage of pores and wear performance of coatings is investigated. Also, wear tracks morphology is investigated to determine the wear mechanism that is responsible for the wear of coatings. From the analysis, it is observed that the formation of cracks as well as micropores is decreased by the addition of carbon nanotubes. Moreover, uniform CNT distribution and good adhesion of coatings with the substrate are the major factors that improve the wear performance of the coated surface.